Energy conservation technique for smart transportation system - Rahul, V; Kowsalya Devi, Ch; Mohammed Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
Electricity is a primary concern everywhere and for everyone. In our daily transportation, we observe most of the time electricity is used unnecessarily and Electric short-circuits occur frequently. Railway coaches are mainly considered in this paper. We have described how to reduce electricity consumption in railway coaches using the raspberry pi and ultrasonic sensors interconnected to the cloud. Considering present smart coaches in railways, the passenger count and their comfort are taken as challenging, but not the production and conservation of electricity. The annual power consumption of Indian Railways is nearly 4% out of countries annual power consumption. Not only in railways systems, this can be further implemented in any other transport systems or in any platforms as well, by this we can reduce the human intervention. Where the loco pilot can control the electricity usage from his cabin, if not it is automated. However, the wireless communication technologies are secured by SSL (Secure Socket Layer). Simply we connect all the required interfaces to pi to acquire the output. Â